Self-spoliation and forms of resistance in total institutions: an exploration of time and space in an Albanian communist regime internment camp - Floridi, Federica; Cataldi, Silvia; Bonaiuto, Marino; Talamo, Alessandra (Frontiers in Sociology, 2025)
The paper explores the daily life within Albanian internment camps during Enver Hoxha's prolonged communist regime, covering the period from 1944 to 1985. Extensive in-depth interviews with former internees underpin the research, which investigates the multifaceted strategies employed by these captives to resist the totalitarian obliteration of time and space, inherent in total institutions. These camps were not merely sites of physical isolation but were ideologically conceived as instruments of political repression, mirroring the Soviet Gulag system. The importance of community relationships for the survival of ex-internees is highlighted, featuring a deep network of mutual aid and long-lasting friendships. This serves as a sharp contrast to the oppressive context. The study reveals a paradoxical dimension to the ex-internees' experience: a strong attachment and reverence toward the locations that brought them great suffering, almost deeming them sacred. In these spaces, solidarity became a form of collective psychological resistance, allowing individuals to reconstruct emotional integrity and assert autonomy despite the brutal regime. This connection to sites of suffering establishes a fundamental foundation of personal and social identity, showcasing the incredible strength of humanity even in the harshest circumstances. It also elucidates the opposing forces of subjugation and resistance within the camp system, revealing the transformative strength of communal ties and the singular bond with these sites of affliction. In exploring these themes, it delves into the complex interplay between individual identity, collective solidarity, and the profound impact of extreme contexts. These findings challenge traditional views on total institutions, emphasizing the dynamic and active role of memory in survivor narratives, where personal and collective histories are reconstructed within the framework of trauma and emotional resilience.